The Impact Of Information Technology Governance On The Quality Of Loan Portfolios (A Field Study On The Syrian Private Banks - محمد , رامي (Latakia University Journal - Economic and Legal Sciences Series, 2021)
The study aimed to know the effect of the governance of technological activities in the banks under study on the quality of loan portfolios provided to their clients and to achieve the purpose of this study, a questionnaire was designed and distributed to workers in the private Syrian banks from administrative levels (managers, internal auditor, head of department, head of department) . The study sample consisted of (180) valid observations for the analysis, and using the appropriate statistical methods to transmit the data, the study reached the following: The presence of an impact of information technology governance at the level applied in the Syrian banks under study in accordance with the COBIT framework in its four fields combined, and individually, on the quality of the loans portfolios of those banks.